RECOMMENDATION FOR THE BEST GAMING PHONE USING THE WEIGHT PRODUCT METHOD - Christy, Tika; Rani, Maha; Ardiansyah, Ricki; Novia, Rini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Mobile phones, as essential telecommunication devices today, are equipped with numerous features. The plethora of mobile phone models, especially gaming phones, requires consumers to be discerning in choosing a phone for everyday use. The problem is that many consumers do not understand how to purchase a phone that meets their specific criteria. The specifications that must be considered when selecting a gaming phone that fits within a budget and meets criteria include performance or specifications, screen quality, battery life, RAM, network connectivity, and price. A decision support system is a part of information systems designed to facilitate decision-making processes based on data or common everyday problems. The Weighted Product (WP) method is typically used in decision-making that involves multiple criteria to be considered simultaneously. Based on the WP method calculations, it was found that the recommended smartphone alternative is determined by the highest vector value (V) ranking according to user-defined criteria. The analysis results indicate that the recommended smartphone alternative is Alternative 1 with a score of 0.376, which is the Infinix GT 10 Pro, due to its comparable specifications to other models but with a more affordable price.